Talent Conversation What They Are, Why They're Crucial, and How to Do Them Right - Smith, Roland (Center for Creative Leadership, 2018)
You as an individual leader are in the best position to have a significant amount of influence over your talented employees. Having effective talent conversations is both a retention strategy and a significant lever for increasing organizational performance
Description based on publisher supplied metadata and other sources
Keywords: Ability; Leadership